2013
DOI: 10.1186/1471-2393-13-46
|View full text |Cite
|
Sign up to set email alerts
|

How effective are the components of active management of the third stage of labor?

Abstract: BackgroundActive management of the third stage of labor is recommended for the prevention of post-partum hemorrhage and commonly entails prophylactic administration of a uterotonic agent, controlled cord traction, and uterine massage. While oxytocin is the first-choice uterotonic, it is not known whether its effectiveness varies by route of administration. There is also insufficient evidence regarding the value of controlled cord traction or uterine massage. This analysis assessed the independent and combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 22 publications
1
24
0
2
Order By: Relevance
“…Earlier researchers found no consistent difference between oxytocin administered with delivery of the anterior shoulder or with delivery of the placenta (Soltani, Hutchon, & Poulose, ). Every facility should have a departmental protocol for oxytocin use in the immediate postpartum period (Sheldon, Durocher, Winikoff, Blum, & Trussel, ). The World Health Organization (), American Academy of Pediatrics and The College (), American Academy of Family Physicians (Evanson & Anderson, ), and AWHONN () recommend oxytocin administration after all births.…”
Section: Recognition and Prevention (Every Patient)mentioning
confidence: 99%
“…Earlier researchers found no consistent difference between oxytocin administered with delivery of the anterior shoulder or with delivery of the placenta (Soltani, Hutchon, & Poulose, ). Every facility should have a departmental protocol for oxytocin use in the immediate postpartum period (Sheldon, Durocher, Winikoff, Blum, & Trussel, ). The World Health Organization (), American Academy of Pediatrics and The College (), American Academy of Family Physicians (Evanson & Anderson, ), and AWHONN () recommend oxytocin administration after all births.…”
Section: Recognition and Prevention (Every Patient)mentioning
confidence: 99%
“…Sheldon et al, in their systematic assessment have documented that the significance of CCT is only if the uterotonic agents are not available or if oxytocin is given intramuscularly. 26 Similarly, Gulmezoglu et al, compared active management performed with and without controlled cord traction in a large WHO multi-center trial and only showed a slight increased risk of severe postpartum hemorrhage in cases without controlled cord traction and concluded that the main component of active management was the use of uterotonic. 27 A Cochrane database meta-analysis by Begley et al, showed that although active management reduced mean blood loss and postpartum hemorrhage (>500 cc), there was no statistically significant reduction in severe postpartum hemorrhage (>1000 cc) for women at low risk for bleeding as well as in mean duration of third stage of labour, which was in contrast to present study.…”
Section: Discussionmentioning
confidence: 99%
“…Debate on appropriate timing of UCC following birth has been ongoing for several decades (even centuries), yet the ideal time still remains unknown. As a result, although the potential benefits of delayed umbilical cord clamping (DCC) have been documented, ‘early’ or ‘immediate’ umbilical cord clamping (ICC) is the most widely used procedure and is part of the active management of third stage of labor; i.e., the period extending from complete delivery of the infant to complete delivery of the placenta ( 1 , 2 ). Although the reasons for this are unclear, a lack of understanding and awareness of the issues associated with UCC are thought to be a major underlying factor ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%